Bleeding management after frenectomy - Britaria Theressy, - (Airlangga University Press (AUP), 2015)
Background: An Aberrant frenum is one of the predisposing factors of periodontal tissue destruction such as gingival recession. The management of an aberrant frenum can be accomplished by frenectomy procedure. The goal of frenectomy is frenum attachment repositioning. Some complications can occur after frenectomy such as pain and bleeding. The purpose of this case report is to explain the management of bleeding after frenectomy. Case: A 20 years old female feels aesthetically discomfort of upper lip. Intraoral examination found a high attachment of frenulum at the upper lip ucosal. One week after scaling frenulum is repositioned with frenectomy procedure. Methods: local anesthesia in the operating area, frenulum is incised with V shape incision using a scalpel no. 15, remove the muscle attachment, then suturing the gingiva with 4.0 silk suture. Patient were instructed restrict the movement of the lips and were prescribed antibiotics, analgesics and mouthwash. One hour after frenectomy bleeding happened in the area of operation. After evaluation on the area of operation, found bleeding with moderate intensity from the gap between gingiva that had been sutured. Case Management: Application of eriodontal dressing in the region of postoperative area to obtain a good adaptation and to cover a narrow area that is still open, thus minimizing the risk of bleeding. Control I day 11, dressing is unattached,sutures are still attached properly. Gingiva’s colour is normal. Conclusion: Periodontal dressing after frenectomy should be done to avoid the occurrence of postoperative bleeding.